2002
DOI: 10.1046/j.0022-3042.2002.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

PK 11195 attenuates kainic acid‐induced seizures and alterations in peripheral‐type benzodiazepine receptor (PBR) protein components in the rat brain

Abstract: Peripheral-type benzodiazepine receptors (PBR) are located in glial cells in the brain and in peripheral tissues. Mitochondria form the primary location for PBR. Functional PBR appear to require at least three components: an isoquinoline binding protein, a voltage-dependent anion channel, and an adenine nucleotide carrier. In the present study, rats received intraperitoneal kainic acid injections, which are known to cause seizures, neurodegeneration, hyperactivity, gliosis, and a fivefold increase in PBR ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 78 publications
2
55
0
Order By: Relevance
“…Thus, it has been suggested that TSPO in glia may play a role in neurodegenerative processes and brain damage. In animal studies, both PK 11195 and Ro5-4864 presented neuroprotective effects against brain injury, which have been suggested to involve neurosteroid activation (Veenman et al, 2002;Veenman & Gavish, 2006Soustiel et al, 2008). Alternatively, it has been suggested that enhanced levels of TSPO in neural cells (due to damage, disease, etc.)…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it has been suggested that TSPO in glia may play a role in neurodegenerative processes and brain damage. In animal studies, both PK 11195 and Ro5-4864 presented neuroprotective effects against brain injury, which have been suggested to involve neurosteroid activation (Veenman et al, 2002;Veenman & Gavish, 2006Soustiel et al, 2008). Alternatively, it has been suggested that enhanced levels of TSPO in neural cells (due to damage, disease, etc.)…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
“…This topic has arisen from the electron microscopic observation that the 18 kDa TSPO protein was organized in clusters of 2-7 molecules on Leydig cell mitochondrial membranes (Papadopoulos et al, 1997). It was also suggested that free TSPO (meaning not in complex with VDAC and ANT) may be present in mitochondrial membranes (Veenman et al, 2002;Liu et al, 2003). This claim further takes into consideration that modulation of steroidogenesis only requires a mitochondrial channel that is www.intechopen.com formed by the mitochondrial TSPO, without participation of VDAC and ANT (Papadopoulos et al, 2006).…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, pre-treatment of rats with PK11195 attenuates the occurrence of seizures in a kainic acid-induced model of seizures [25], and another TSPO-selective ligand, XBD173, induces neurosteroid synthesis and is anxiolytic in humans without benzodiazepine-like side effects [26].…”
Section: Tspo As a Target For Pet Imagingmentioning
confidence: 99%